Training in the Processing of Vegetable Catfish Nuggets for Lauk Babakan Village PKK Women, Bogor - Riani Prihatini Ishak; Nisa Rahmaniyah Utami (LPPM UIKA Bogor, 2022)
Residents of Kampung Lauk Babakan Bogor have their main source of income from catfish farming. So that their lives are guaranteed through their income and work, especially after the pandemic, the people of Kampung Lauk Babakan must be able to act creatively to increase the economic value of catfish. Residents of Kampung Lauk Babakan tend to sell post-harvest catfish directly to consumers or distributors at relatively low prices. Processing catfish into vegetable nuggets can increase the economic value of catfish. For this purpose, the STP Bogor community service agency provided training to the people of Kampung Lauk Babakan, especially PKK women, about processing catfish into vegetable nuggets. Training activities are expected to be able to increase the skills and creativity of the community to manage catfish. Community service is carried out by providing counseling about the nutritional content of catfish and training in processing it into vegetable catfish nuggets to increase its economic value. The result of this dedication to Kampung Lauk Babakan is an increase in knowledge about the nutritional content of catfish and an increase in creativity in processing catfish as a solution to increase the selling value of catfish.